Security and Privacy Issues in Cloud Computing. Issue 1 (August 2021) - Alenizi, Bayan A.; Humayun, Mamoona; Jhanjhi, NZ
Abstract: The idea of Cloud Computing (CC) provides dynamically scalable services that are delivered over the Internet as a service. The key driver of the cloud is economic benefits, as it aims to minimize capital expenditure as well as operating expenditure. There are still some problems to be overcome in order for this to become reality. One of the important issue is security and privacy concerns, which has been addressed by many researchers but still the problem persist. Security assurance is an important driver for cloud adoption and for increasing cloud deployment. To provide a detailed overview of existing cloud security challenges and mitigation strategies, this paper provides a comprehensive survey of underlying cloud security and privacy issues and concerns along with countermeasures. Further; as a contribution in research, we have provided a framework to address the security and privacy concerns in CC. Proposed framework uses hybrid authentication mechanism for the security of CC. The study provides a deeper insight to the researchers and practitioners about CC and underlying security and privacy concerns along with countermeasures and a novel solution.